The Impact of Islamic Values-Based Management on Educational Quality in Islamic Schools - Siti Fatinnah Binti Abd Rahman; Jhon Smith (JMPI: Jurnal Manajemen, Pendidikan dan Pemikiran Islam, 2024)
This study investigates the role of Islamic values-based management in enhancing the quality of education in Islamic schools. The research explores how principles rooted in Islamic ethics—such as honesty, responsibility, discipline, and compassion—can significantly impact the academic and moral development of students. Utilizing a mixed-method approach, this study analyzes data from surveys conducted with teachers, students, and administrators across several Islamic schools, alongside qualitative interviews to provide deeper insights into the lived experiences of participants within these environments. The findings reveal a positive correlation between Islamic values-based management and educational quality, demonstrating that schools prioritizing these values see improvements in student engagement, academic achievement, and character development. The research also discusses the implications for educational administrators and policy-makers, emphasizing the importance of incorporating Islamic ethical frameworks into school management practices. Recommendations include enhanced teacher training on Islamic values, curriculum development that integrates ethical teachings, and active parental involvement to reinforce these values both in and out of the school setting. The study concludes that Islamic values-based management offers a holistic approach to education that not only fulfills academic standards but also supports the moral and ethical growth of students, aligning with the comprehensive goals of Islamic education.